2010
DOI: 10.1590/s0004-28032010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus and impaired glucose tolerance in patients with decompensated cirrhosis being evaluated for liver transplantation: the utility of oral glucose tolerance test

Abstract: The prevalence of diabetes mellitus, impaired glucose tolerance, insulin resistance and protein calorie malnutrition is high in cirrhotic patients on the waiting list for liver transplantation. There were more infectious complications and/or deaths in a 3-month follow-up period in patients with diabetes mellitus diagnosed by oral glucose tolerance test. Oral glucose tolerance test seems to be indicated as a routine practice in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
16
0
2
Order By: Relevance
“…40 The proportion of diabetic patients on the transplantation waiting list was high in our study, a result that has also been described in other case series. 22 Our results showed that a considerable number of nondiabetic patients developed diabetes mellitus after transplantation, which was also similar to data described in other studies. 23 The majority of studies that have evaluated glycemia in hospitalized patients usually define it as one or several values that are altered at one period of time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…40 The proportion of diabetic patients on the transplantation waiting list was high in our study, a result that has also been described in other case series. 22 Our results showed that a considerable number of nondiabetic patients developed diabetes mellitus after transplantation, which was also similar to data described in other studies. 23 The majority of studies that have evaluated glycemia in hospitalized patients usually define it as one or several values that are altered at one period of time.…”
Section: Discussionsupporting
confidence: 92%
“…20,21 On the other hand, diabetes is a frequent comorbidity in patients on the liver transplantation waiting list, presenting in 65% of them. 22 Despite this fact, there is scant evidence that hyperglycemia is a risk factor for negative outcomes in patients that have undergone transplantations, even though, in general, diabetes is associated with a worse outcome in liver transplantation patients. The prevalence of post-transplantation diabetes is as high as 31-38%, 23 and these patients are at a higher risk for cardiovascular complications, such as high blood pressure and coronary disease, as well as a higher mortality rate, compared with those patients that do not develop diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of advanced liver cirrhosis, eventually the pancreatic β cells cannot continue to increase the secretion of insulin to compensate for the insulin resistance. Thus, relatively insufficient insulin secretion and impaired glucose tolerance appear (Bragança and Álvares-da-Silva, 2010). The liver cirrhosis patients in our study were precisely at this stage.…”
Section: Discussionmentioning
confidence: 79%
“…The concept of hepatic diabetes was introduced as early as 1906 (Bragança and Álvares-da-Silva, 2010). It refers to diabetes brought about by chronic liver disease or liver cirrhosis which may be related to insulin resistance (Arai et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of IGT and DM based on the OGTT was 61% (IGT, 23%; DM, 38%) in compensated cirrhotic patients 7 and 90.3% (IGT, 25.8%; DM, 64.5%) in decompensated cirrhotic patients. 23 However, an accurate diagnosis of DM is sometimes difficult in cirrhotic patients because FPG and HbA1c are not always available. HbA1c levels tend to be lower in cirrhotic patients because of the short lifespan of erythrocytes caused by hypersplenism.…”
Section: T He Present Study Describes a Novel Test For Dis-mentioning
confidence: 99%